Sutures versus staplers for skin closure in laparotomy patients: a prospective study - Sharma, Gopal; Prasher, Nivedita (International Journal of Research in Medical Sciences, 2020)
Background: Every surgeon wants cosmetically acceptable scars along with optimal healing. Good tissue union and cosmetically acceptable scars are vital for ideal surgical practice. A basic need for skin closure is a good approximation. Apart from cosmetically good scars, it is also necessary that the skin closure technique should be technically easy, speedy, economical and acceptable. Methods: The study was conducted on 100 patients on whom elective abdominal surgeries were performed. Patients were divided into two groups with 50 patients in each group after matching the parameters like age, co morbid conditions, using simple random sampling technique. All operations were performed by one consultant. In group A, Skin was approximated with vertical mattress sutures while in group B, staplers were used to close the wound. Results: The age of the patients varied from 16 to 85 years. The average time taken for skin closure for suture group (A) was found to be 300sec (±20.78) and for stapler group was found to be 120sec (±16.50) respectively. Wound infection was found in 10 patients (20%). In stapler group 4 (8%) and in suture group 6 Patients (12%) had post-operative wound infection. Conclusions: Cosmesis is essential and necessary in modern surgical practice. It also reflects surgical expertise.